Neuroticism and extraversion among aurally handicapped adults - Srinivasan P (Journal of All India Institute of Speech and Hearing, 1970)
There are many studies in the literature on the personality characteristics of the hearing impaired. This study compares the adventitiously aurally rehabilitated with the normal hearing on two dimensions of personality, viz., Neuroticism and Extraversion. The Eysenck Personality Inventory was administered to 100 subjects of normal hearing and 78 subjects of adventitious aural rehabilitation.